2004
DOI: 10.1063/1.1779051
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the history force acting on oscillating fluid spheres at low Reynolds number

Abstract: This paper reports an experimental investigation of isolated fluid particles rising (or falling) in a quiescent viscous liquid placed in an oscillating frame. Our goal is to carry out the first quantitative analysis of the effect of the history force on clean and spherical drops and bubbles. The average terminal Reynolds number is less than 0.5, the Strouhal number ranges from 1 to 25, and the Weber number ranges from 0.006 to 0.5. The particle motion is tracked by using a high-speed video camera and an accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Maxey et al (1996) found that up to Re p ≈ 17 the standard form (1.2) "may be quite adequate in practice even though not justified by theory". In an experimental study Abbad & Souhar (2004) considered particle Reynolds numbers of up to 0.5 and found the standard form to remain valid. In our simulations the typical Re p is smaller or on the order of unity (except for ̺ = 0 and St > 2, when it becomes larger than 3).…”
Section: The Stokes Numbermentioning
confidence: 99%
“…Maxey et al (1996) found that up to Re p ≈ 17 the standard form (1.2) "may be quite adequate in practice even though not justified by theory". In an experimental study Abbad & Souhar (2004) considered particle Reynolds numbers of up to 0.5 and found the standard form to remain valid. In our simulations the typical Re p is smaller or on the order of unity (except for ̺ = 0 and St > 2, when it becomes larger than 3).…”
Section: The Stokes Numbermentioning
confidence: 99%
“…In non-chaotic flows, the history force was shown to have important effects [21][22][23][24][25]. A particularly interesting example is an experiment [26,27] that points out the determining importance of memory in the motion of microbubbles propelled by ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature there are many experimental studies on the effect of hydrodynamic forces acting on macroscopic particle motion at low and moderate particle Reynolds numbers [10][11][12][13][14]. This prompted us to investigate, numerically and experimentally, how each hydrodynamics force affects the particle motion at high particle Reynolds numbers.…”
Section: Resultsmentioning
confidence: 99%
“…Results obtained recently for the motion of particles in supersonic flow across oblique shocks showed that the Basset force could be even more significant than the Stokes drag force [10]. Abbad et al [11,12] did experiments to study a free-falling rigid sphere in a quiescent incompressible Newtonian fluid, placed in an oscillating frame. They investigated, numerically, the effect of the history force acting on the sphere at small-particle Reynolds numbers (Re p ≤ 2.5).…”
Section: Introductionmentioning
confidence: 99%